Options treatment of periodontitis in the acute stage (К04.7), excluding «period open tooth» (Эндодонтия Today, 2020)
This article deals with the conservative treatment of chronic periodontitis in the acute stage without the «open period of the tooth» and mandatory appointment of antibiotics and anti-inflammatory drugs. 17 clinical cases are presented with a detailed description of the methods of treatment and the results. 16 patients aged 28-65 years with a diagnosis К04.7 were treated. Positive results confirmed clinically and radio graphically after 6-12 months. The treatment takes place without complications and complete recovery of bone structures in the former foci of destruction is faster in teeth with one root canal, do not expose previously endodontic treatment.